Role of non-invasive ventilation in management of Plasmodium vivax malaria presenting as acute respiratory distress syndrome: A case report (Indian Journal of Case Reports, 2018)
Plasmodium vivax malaria has been rarely found to be associated with acute respiratory distress syndrome (ARDS), and very few cases have been reported with ARDS as the presenting complication. In majority of the reported cases, invasive mechanical ventilation has been used for the management of respiratory failure in P. vivax-associated ARDS. We report a case of vivax malaria presenting as ARDS which was managed successfully with antimalarial drugs and non-invasive ventilation.